2007
DOI: 10.1074/jbc.m611642200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Inactivation of Plasminogen Activator Inhibitor-1 by a Small Molecule Inhibitor

Abstract: The inactivation of plasminogen activator inhibitor-1 (PAI-1) by the small molecule PAI-1 inhibitor PAI-039 (tiplaxtinin) has been investigated using enzymatic analysis, direct binding studies, site-directed mutagenesis, and molecular modeling studies. Previously PAI-039 has been shown to exhibit in vivo activity in various animal models, but the mechanism of inhibition is unknown. PAI-039 bound specifically to the active conformation of PAI-1 and exhibited reversible inactivation of PAI-1 in vitro. SDS-PAGE i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 65 publications
5
97
0
Order By: Relevance
“…Arg-76 and Tyr-79 in ␣-hD and Thr-93, Thr-94, and Asp-95 in ␤-s2A have been suggested to be involved in binding (see Fig. 9A) (53). Notably, all of these residues are within 5 Å from the AZ3976 ligand in the present structure (Fig.…”
Section: Discussionmentioning
confidence: 48%
“…Arg-76 and Tyr-79 in ␣-hD and Thr-93, Thr-94, and Asp-95 in ␤-s2A have been suggested to be involved in binding (see Fig. 9A) (53). Notably, all of these residues are within 5 Å from the AZ3976 ligand in the present structure (Fig.…”
Section: Discussionmentioning
confidence: 48%
“…The most extensively studied PAI-1 inactivating compound to date, tiplaxtinin, binds to active but not latent PAI-1 (11). This selectivity is a consequence of structural differences in the binding site between the two serpin conformations.…”
Section: Resultsmentioning
confidence: 99%
“…These associations have made PAI-1 an attractive pharmaceutical target. However, despite extensive studies, only a few small molecule inhibitors have been identified thus far (7)(8)(9)(10)(11)(12)(13)(14)(15)(16), and the majority of these are poor pharmaceutical candidates as they have relatively low affinity for PAI-1 and are unable to inactivate PAI-1 bound to its plasma cofactor vitronectin.…”
mentioning
confidence: 99%
“…In summary, inhibition of PAI-1 could be therapeutically beneficial in treating MS, using small molecular weight PAI-1 inhibitors now available [53,54].This would provide a dual palliative approach whereby leucocyte migration and inflammation are reduced, allowing efficient removal of fibrin, which could potentially decrease axonal/neuronal damage and reduce frequency of disease relapses in MS patients.…”
Section: Discussionmentioning
confidence: 99%